The Role of Throughput Accounting in Maximizing Profits: Application Search in the General Company for Textile Industry / Cotton Factory - Al-Halbousi, Jamal Noori Dahham; Ali, Miyead Hamid (Journal of Economics and Administrative Sciences, 2021)
Throughput accounting is concerned with a throughput measurement process to determine the efficiency of the company, to know the problems and obstacles it suffers from, to determine their causes and ways to address them.The research problem is represented by the following question: does the application of a throughput accounting lead to maximizing the company’s profits? The aim of the research is to demonstrate the importance of throughput accounting, which is one of the tools of management accounting in providing an efficient information system that provides the company’s management with the information it needs to improve its production processes, increase a throughput, and thus maximize its profits. The researcher reached a set of conclusions; the most important of which is that a throughput accounting provides a number of indicators such as (the margin of a throughput, the rate of a throughput and the time of throughput) that help in measuring performance and identifying the problems faced by the company and the means to address them. The researcher recommends that the company should apply a throughput accounting instead of the traditional system to provide measures and indicators that help increase a throughput and focus on increasing the throughput margin and reducing inventory and operating costs to the lowest possible level